2010
DOI: 10.1007/s00467-009-1432-2
|View full text |Cite
|
Sign up to set email alerts
|

Growth and body composition in very young SGA children

Abstract: Infants with a very low birth weight are at risk of a reduced number of nephrons predisposing to kidney disorder, hypertension, and metabolic syndrome. Approximately 3% of infants are born small for gestational age (SGA), defined as birth weight and/or length at least 2 SD below the mean for gestational age (GA), independently of whether these children are born prematurely or at term. About 10% of these children do not show postnatal catch-up growth and remain of short stature during childhood. Most of these i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 70 publications
(70 reference statements)
2
39
0
Order By: Relevance
“…Arterial hypertension is also increasingly important in children and adults born prematurely, especially before 33 weeks of gestation and in children born with intrauterine hypotrophy (small for gestational age, SGA) [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Arterial hypertension is also increasingly important in children and adults born prematurely, especially before 33 weeks of gestation and in children born with intrauterine hypotrophy (small for gestational age, SGA) [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have historically examined the Dutch Famine Birth Cohort, which consists of men and women born as term singletons in the western part of The Netherlands during or immediately following the Dutch Famine of 1944–1945 (de Rooij et al 2010; Stein et al 1972). The use of this particular cohort allowed the opportunity to examine the effects of one particular adverse exposure—starvation during pregnancy, even as a function of trimester—which was associated with outcomes such as schizophrenia, type 2 diabetes mellitus, cardiovascular disease, other metabolic disorders, and decreased cognitive function later in life (Argente et al 2010; Barker and Clark 1997; de Rooij et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…9 High birthweight, as well, has been shown to have serious adverse health outcomes in both developing children and later in life. 10 Previous studies have shown high birthweight as a risk factor for insulin resistance, 11 obesity 12 and cancers such as leukemia and breast, prostate and colon cancers.…”
Section: Introductionmentioning
confidence: 99%